Optimalisasi Pengelolaan Wakaf Uang untuk Kesejahteraan Umum - Muhammad Alfin Syauqi (Universitas Syiah Kuala, 2014)
Wakaf, an obligatory religious donation for certain Muslim, has usefully flexible values and been a significant thing that can improve for prosperity, especially in Semarang. This research explores the donation that is done by BMH Semarang, constraints and step to optimize the management of it for prosperity. Semarang territory is too wide to be used by the BMH Semarang to manage the donation in order to increase the wealth of people in Semarang. However, the BMH of Semarang has not been able to optimize its management. The constraints faced are lack of Human Resources and competence, society culture that is illiterate on the matter, lack of publication and the support of the local government. Steps taken to optimize are to increase the human sources to be more professional and understanding, people understanding, the reference on the issue for the business sectors, the acceptance of the donation and coordinate with the government. The Optimalization of Wakaf Money for Public Prosperity